2018
DOI: 10.1037/cns0000148
|View full text |Cite
|
Sign up to set email alerts
|

“False memory” is a linguistic convenience.

Abstract: The term false memory describes outcomes to various procedures and techniques, such as coming to believe that suggested false events occurred, acceptance of postevent misinformation, and recognition of critical lures in the Deese−Roediger−McDermott (DRM) procedure. The literature to date has indicated that these memory errors intercorrelate poorly, if at all. However, issues with sample size and measurement reliability may have affected prior estimates. This study examined links among these 3 techniques in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 67 publications
2
35
0
Order By: Relevance
“…Our correlational results showed no statistically significant relationship between DRM false memories (both recall and recognition) and false memories as elicited by the memory conformity paradigm. This echoes previous work showing that false memories as measured by different paradigms evince a weak relationship (i.e., Bernstein et al, 2018;Ost et al, 2013;Otgaar & Candel, 2009;Patihis et al 2013;Zhu et al, 2010). Our results imply that spontaneous false memories and false memories induced by suggestion are formed in different ways.…”
Section: Discussion and Limitationssupporting
confidence: 86%
See 2 more Smart Citations
“…Our correlational results showed no statistically significant relationship between DRM false memories (both recall and recognition) and false memories as elicited by the memory conformity paradigm. This echoes previous work showing that false memories as measured by different paradigms evince a weak relationship (i.e., Bernstein et al, 2018;Ost et al, 2013;Otgaar & Candel, 2009;Patihis et al 2013;Zhu et al, 2010). Our results imply that spontaneous false memories and false memories induced by suggestion are formed in different ways.…”
Section: Discussion and Limitationssupporting
confidence: 86%
“…On the other hand, the research on spontaneous false memories has indicated that children are less susceptible to false memories (Anastasi & Rhodes, 2008;Metzger et al, 2008). This implies that false memory does not refer to a unitary concept and that different methods used to induce false memories produce different outcomes, which are carried by different mechanisms (Bernstein, Scoboria, Desjarlais, & Soucie, 2018). To further examine this, researchers should follow two important steps in their investigations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings, combined with converging current research (Bernstein, Scoboria, Desjarlais, & Soucie, 2017) and past research (e.g. Ost et al, 2013), suggest that it may be difficult to identify false-memory prone individuals who are especially susceptible to memory distortions in different contexts.…”
Section: Discussionmentioning
confidence: 58%
“…However, other studies have failed to find a relationship between misinformation and DRM false memories (Calvillo & Parong, 2016;Monds, Paterson, & Kemp, 2017;Ost et al, 2013), between DRM and false event suggestion (Otgaar & Candel, 2011), or between imagination inflations for childhood events and for simple actions performed in the laboratory (Calvillo et al, 2018). Only two studies to date have examined correlations between false memories in misinformation, DRM, and false event suggestion manipulations, and both failed to find any correlations among them (Bernstein, Scoboria, Desjarlais, & Soucie, 2018;Patihis, Frenda, & Loftus, 2018). Overall, the research describes largely null relationships between false memories of different paradigms, but none so far have explored false memories specifically in the misinformation, DRM, and imagination inflation paradigms all within subjects.…”
Section: Theoretical Foundationsmentioning
confidence: 99%